(untitled) - Kremen, Branislav (Doprava a spoje, 2005)
Nowadays are broadband technologies more popular than ever before. There are more reasons of this growing trend. Main reasons are incufficient speed of current analog technologies. There are more closely described modern and most popular technologies of access to internet in this articel.